Dynamic holographic interconnects that use ferroelectric liquid-crystal spatial light modulators. - O'Brien, D; Mears, R; Wilkinson, T; Crossland, W (1994)
Dynamic interconnect holograms are designed by the use of a simulated annealing algorithm and written to a 128 × 128 pixel ferroelectric spatial light modulator that is used in a binary-phase mode. Dynamic holograms are used to implement a 2 × 2 crossbar with single-mode fiber inputs and outputs, which function with as high as 27 dB of isolation between output ports. The principle is extended to two-dimensional interconnection holograms, and arbitrary fan-out to as high as 64 points is demonstrated with good performance. Images of interconnection holograms are transferred from the spatial light modulator to an optically addressed spatial light modulator that is used in a binary-phase mode. The addition of a fixed array generator computer-generated hologram permits replication of the hologram image, thus creating a larger hologram with a high space-bandwidth product on the optically addressed spatial light modulator. Results of a preliminary experiment are presented.